IMPLEMENTASI FRONT END PADA DIGITALISASI PEMESANAN PERCETAKAN BERBASIS MOBILE WEB (STUDI KASUS: PERCETAKAN MAS YAN’S BAYUREJA - Indriyani, Putri; Suhendri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid growth of internet technology has transformed various business processes, including printing services that require efficiency and accuracy in order management. Conventional methods used by Mas Yan’s Printing, such as in-person and WhatsApp-based orders, often result in inefficiency, data loss, and customer dissatisfaction. This study aims to implement a mobile web- based digital ordering system with a focus on the frontend to improve service accessibility and operational effectiveness. The development process applied the Waterfall method, starting from system analysis, design using UML diagrams, coding with Laravel framework along with HTML, CSS, and JavaScript, and testing through Black Box method. The system provides several features including product catalog browsing, order placement, digital payment with proof upload, shopping cart management, and chat communication between customers and admin. Testing results show that all implemented features run properly and fulfill user requirements. The mobile web platform successfully reduces manual errors, shortens order processing time, and improves order data management. This implementation enhances customer convenience in accessing printing services and supports the business in reaching wider markets while maintaining competitive advantage.